VALIDITAS MEDIA POSTER BERBASIS AUGMENTED REALITY UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS IV SD - Siti Aini Kholaifah; Novialita Angga Wiratama; Wendri Wiratsiwi (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to test the validity of Augmented Reality-based poster media to improve learning outcomes for fourth-grade students at Gempolpading Elementary School. Most students experience difficulty understanding learning materials due to the limited use of innovative media. Therefore, the availability of innovative, technology-based learning media is essential to create interactive and meaningful learning experiences. Augmented Reality-based poster media is designed to integrate visual media with interactive three-dimensional displays of objects in the real world through a mobile device camera. This approach helps students visualize abstract concepts in a more concrete and understandable way. This study used a Research and Development (R&D) method using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects were 19 fourth-grade students at Gempolpading Elementary School. Media validity was measured based on assessments by three expert validators: a media expert lecturer, a language expert lecturer, and a material expert lecturer, each of whom was tasked with reviewing, providing input, and assessing the feasibility of the developed media. The data collection instruments used included an expert validation questionnaire and a test instrument. The assessment results from all validators indicated that this learning media was categorized as highly valid. The media experts received 100% of the assessments, 96% of the assessments from the language experts, and 96% of the assessments from the material experts, all of which were in the very good category. Based on these findings, this Augmented Reality technology-based poster learning media was deemed highly suitable for use in the learning process.